Evaluation of chemopreventive activity of glutamine by the comet and the micronucleus assay in mice's peripheral blood - Oliveira, Rodrigo Juliano; Baise, Evelyn; Mauro, Mariana de Oliveira; Pesarini, Joao Renato; Matuo, Renata; da Silva, Ariane Fernanda; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mario Sergio (Elsevier B.V., 2009)
This research has evaluated the effects of enteral supplementation of glutamine in clastogens and genotoxic damages caused by the acute administration of cisplatin. For this. it was utilized Swiss mice distributed in eight experimental groups: control, cisplatin, glutamine, in three different doses and the combination of these with cisplatin. The results show that the glutamine was present in neither genotoxic nor mutagenic activity. When in association with glutamine and cisplatin, in simultaneous treatment, it was verified the frequency decreased of micronuclei and comets. The damage reduction percentages to the micronucleus ranged from 95.4 to 91.8% after 24 h of administration of these compounds and 76.7 to 56.8% after 48 h. In the same time the damage reduction percentages to the comet test ranged from 117.0 to 115.0%. The results suggest that glutamine is capable of preventing genotoxic and mutagenic damage according to the experimental design proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cisplatin; Glutamine; Micronucleus; Comet; Chemoprevention